Development of a thermodynamic model of aqueous solution suited for foods and biological media. Part B: Prediction of standard formation properties. (26th November 2014) - Toure, Oumar; Audonnet, Fabrice; Lebert, André; Dussap, Claude‐Gilles
Abstract In food and biological processes, aqueous complexes cover a wide diversity of species and the presence of several phases. The modelling of such processes must take into account these specificities, which require a generalization of the existing thermodynamic models of aqueous solutions. The chemical potential (the molar Gibbs free energy) of a given compound is an important variable to characterize the physical‐chemical properties at equilibrium. Its value depends on two parameters: the Gibbs free energy of formation and the activity coefficient. Both are linked to a chosen reference state. Then, the main thermodynamic modelling task consists in the prediction and/or the collection of formation properties data and in the development of a predictive model of activity coefficients. In this study, a method of prediction of the gas phase formation properties of several organic molecules of interest in foods and biological media using the same input data as those of the COSMO‐RS model (i.e., results of quantum DFT/COSMO calculations) is introduced. This kind of fully predictive approach allows the treatment of conformations. This is its main advantage compared to classical group contribution methods. For fifteen of the studied molecules, the Gibbs free energies of formation predicted at infinite dilution in water are also calculated and compared to experimental data.